Synthesis and Physicochemical Characterization of Pamoate-Intercalated Zinc-Aluminium Layered Double Hydroxide Hybrid Nanocomposite - Jubri @ Mohd Zufri, Zaemah (2006)
Layered organic-inorganic hybrid nanocomposites were prepared by using pamoate ion (PA) as a guest into Zn-Al layered double hydroxide (Zn-Al-LDH) inorganic host by co-precipitation technique. Two methods of aging used in the synthesis process were conventional oil bath and microwave-assisted methods. The Zn to Al molar ratio of the mother liquor was kept constant at 4 at the beginning of the synthesis with concentration of PA, 0.02 M. As the result of successful intercalation of pamoate ion into the interlayer structure of Zn-Al-LDH, an expansion of the interlayer spacing from 8.9 Å in the layered double hydroxide (ZAL) to 18.1 Å in the nanocomposite (ZAP) could be observed in the powder X-ray diffractogram. The advantage of using microwave-assisted method is that the time for aging process is shortened to only 15 to 30 minutes to achieve a well-ordered layered nanocomposite materials compared to 18 hours to age the sample if conventional oil bath method is used to synthesis the nanocomposite. Nanocomposite prepared using various Zn to Al molar ratios 2, 3, 4, 5, 6, 7 and 8 gave a well-ordered nanolayered structure. The effect of various Zn to Al ratios on the properties of layered organic-inorganic hybrid nanocomposite materials show that the BET surface area increases as the Zn to Al molar ratio increases. Nanocomposite prepared from various Zn to Al molar ratios using ion-exchange method, resulted in less ordered nanocomposite materials, with BET surface area in the range of (20.6 - 27.4) m2/g. Thermal decomposition of the nanocomposite was studied by heating the sample at 100-1000˚C under atmospheric condition. The layered structure of the nanocomposite collapsed when the sample was heated at 350˚C or higher and the formation of ZnO phase was observed at 400˚C or higher. Further heating at 1000˚C, resulted in the formation of ZnAl2O4 phase. It was also found that the release of PA anions from the interlamellae of the nanocomposite was controlled by the first order kinetics at least at the beginning of the reaction up to 7 hours. At the end of rapid release rate, the amount of PA released into the aqueous solution at various initial pH values was 16%, 20% and 30% for pH 2, pH 11 and pH 12, respectively.